Potential Analysis of Forest Stand Inventory in Production Forest Management Unit (KPHP) Nunukan IV, Nunukan Regency-North Kalimantan - Andi Almarief (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2018)
This research aims at (1) to determined the potential, the structure and speciescomposition of forest stands in KPHP Nunukan IV for the basis of forest governance andmanagement of the plan.This research uses data from forest inventories KPHP that implementedin July 2017. Tally sheet data from the field was classified by the growth rate, diameter class and species group and then was calculated for number of stems and volume. The results of this research are 1) from 50 plots retrieved 79 species. 2) Species compotition is dominated by Shorea with average volume 175,31 m3/ha. 3) Stand structure,  the total number of trees 137 stems/ha and volume 245,01 m3/ha. Shorea dominate 90 stems/ha and volume175,31 m3/ha.4) for seedlings obtained INP At the highest level is meranti by 45,93%, Kapur by 14,14 % and Keruing by 14,14%. The highest INP of saplings on the type of Meranti at 66,79%, Guava 30,18 % and 19,84 % Medang. At the highest level of pole INP obtained on the type of Meranti at 94,7 % , Mendarahan 24,01% and Jambu-Jambu 21,09%. At the level of the tree has the largest INP Meranti 88,51%, Medang 30,64% dan Keruing 24,49%.